The simulation and analysis in fading channel mode for the performance of a DOA estimation technology, applied to circular ring arrays - GU Yan-tao1; XU Sheng-yu2; XIONG Si-min2; XIE Xian-zhong2 (Tongxin xuebao)
As one of the key technology in the third generation mobile communication, the smart antenna can effectively increase the capacity and reduce the co-channel interference. Since the circular arrays are commonly used in TD-SCDMA system, this paper studies a DOA estimation method by using an advanced ESPRIT algorithm, which is applicable to circular ring arrays, and the corresponding beamforming algorithm. At the last of the paper, we pay attention to the performance of aforementioned algorithm and analysis it from different aspects according to the simulation results in uplink fading channel mode.